2020
DOI: 10.1248/bpb.b19-01069
|View full text |Cite
|
Sign up to set email alerts
|

Three-Dimensional Culture of Umbilical Cord Mesenchymal Stem Cells Effectively Promotes Platelet Recovery in Immune Thrombocytopenia

Abstract: Mesenchymal stem cells (MSCs) can effectively regulate immune cell functions and therefore are promising for the treatment of autoimmune disorders, such as immune thrombocytopenia (ITP). Recent research has shown that three-dimensional (3D) culture method have many advantages over conventional culture with respect to MSC secretion and immunogenicity. In this study, 2D and 3D cultured MSCs were used to evaluate cytokine secretion, extracellular matrix (ECM) gene expression, immune regulatory activity, and thera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 54 publications
0
10
0
Order By: Relevance
“…One research also indicated that the expressions of HLA-G, IDO1, PTGS2 and TGF-β1, which were closely related to immune regulation, were higher in 3D culture than those in 2D culture. Further, 3D cultured MSCs could inhibit the proliferation of activated lymphocytes more effectively [17]. Here, we compared the stemness and immunomodulatory ability between 2D and 3D UC-MSCs and found that 3D culture did preserve the stemness, T cell proliferative inhibition and the expression of anti-in ammatory cytokines such as IL-10 and TGF-β of long-passaged UC-MSCs.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…One research also indicated that the expressions of HLA-G, IDO1, PTGS2 and TGF-β1, which were closely related to immune regulation, were higher in 3D culture than those in 2D culture. Further, 3D cultured MSCs could inhibit the proliferation of activated lymphocytes more effectively [17]. Here, we compared the stemness and immunomodulatory ability between 2D and 3D UC-MSCs and found that 3D culture did preserve the stemness, T cell proliferative inhibition and the expression of anti-in ammatory cytokines such as IL-10 and TGF-β of long-passaged UC-MSCs.…”
Section: Discussionmentioning
confidence: 88%
“…One study found several genes closely related to immune regulation, such as human leukocyte antigen (HLA)-G, indoleamine 2,3-dioxygenase (IDO)-1, prostaglandin synthase (PTGS)-2 and transforming growth factor (TGF)-β1 were more highly expressed after 3D culture than that after 2D culture. Further, 3D cultured MSCs could inhibit the proliferation of activated lymphocytes more effectively [17]. However, the mechanism of maintaining cellular immunomodulatory ability in 3D culture has not been reported, and exploring this mechanism provides an experimental basis for further elucidating the immunomodulatory characteristic of MSCs in 3D culture.…”
Section: Introductionmentioning
confidence: 99%
“…However, the development of 3D culture methods has improved the ability to amplify BM-MSCs. The BM-MSCs amplified through this method are superior to those produced by traditional culture methods in terms of secretion and immunogenicity, and they also have been found to improve the body weight, spleen index, platelet index, and bone marrow homing ability in a mouse model of ITP [54]. Cytological experiments performed in vitro have also shown that BM-MSCs regulate the balance of Th1/Th2 cell activity in ITP, thereby inhibiting the secretion of IL-2 and IFN-γ by Th1 cells and promoting the secretion of IL-4 by Th2 cells, which then upregulate CD4+ CD25+ CD25+ T cells and induce immune tolerance [55].…”
Section: The Clinical Application Of Bm-mscs In Patients With Itpmentioning
confidence: 99%
“… 156 , 157 Due to the immunomodulatory effect of MSCs, MSCs transplantation has shown a certain therapeutic effect on ITP in vivo and in vitro, and in the clinic. 158 161 …”
Section: Mirnas Abnormally Expressed In Itpmentioning
confidence: 99%